Prosthetic rehabilitation of a preschooler with induced anodontia - A clinical report - Shivayogi M Hugar; Anand L Shigli; P V Ravindranath Reddy; N M Roshan (Wolters Kluwer Medknow Publications, 2011)
A case of prosthetic rehabilitation with complete dentures for a three year nine months old child is presented. Dental prosthesis are frequently used to avoid psychologic, speech, or swallowing problems in preschooler children. The case was followed up for a period of three years. These prosthesis were modified as the child grew and as the permanent teeth erupted into the oral cavity the dentures were trimmed from the areas of erupting teeth to facilitate their eruption.